Factors associated with prenatal folic acid and iron supplementation among 21,889 pregnant women in Northern Tanzania: A cross-sectional hospital-based study - Ogundipe Olukemi; Hoyo Cathrine; Østbye Truls; Oneko Olola; Manongi Rachael; Lie Rolv; Daltveit Anne (BMC, 2012)
Abstract Background Folate and iron deficiency during pregnancy are risk factors for anaemia, preterm delivery, and low birth weight, and may contribute to poor neonatal health and increased maternal mortality. The World Health Organization recommends supplementation of folic acid (FA) and iron for all pregnant women at risk of malnutrition to prevent anaemia. We assessed the use of prenatal folic acid and iron supplementation among women in a geographical area with a high prevalence of anaemia, in relation to socio-demographic, morbidity and health services utilization factors. Methods We analysed a cohort of 21,889 women who delivered at Kilimanjaro Christian Medical Centre (KCMC), Moshi, Tanzania, between 1999 and 2008. Logistic regression models were used to describe patterns of reported intake of prenatal FA and iron supplements. Results Prenatal intake of FA and iron supplements was reported by 17.2% and 22.3% of pregnant women, respectively. Sixteen percent of women reported intake of both FA and iron. Factors positively associated with FA supplementation were advanced maternal age (OR = 1.17, 1.02-1.34), unknown HIV status (OR = 1.54, 1.42-1.67), a diagnosis of anaemia during pregnancy (OR = 12.03, 9.66-14.98) and indicators of lower socioeconomic status. Women were less likely to take these supplements if they reported having had a malaria episode before (OR = 0.57, 0.53-0.62) or during pregnancy (OR = 0.45, 0.41-0.51), reported having contracted other infectious diseases (OR = 0.45, 0.42-0.49), were multiparous (OR = 0.73, 0.66-0.80), had preeclampsia/eclampsia (OR = 0.48, 0.38-0.61), or other diseases (OR = 0.55, 0.44-0.69) during pregnancy. Similar patterns of association emerged when iron supplementation alone and supplementation with both iron and FA were evaluated. Conclusions FA and iron supplementation are low among pregnant women in Northern Tanzania, in particular among women with co-morbidities before or during pregnancy. Attempts should be made to increase supplementation both in general and among women with pregnancy complications.